Predictive Value of Heart Rate and Blood Pressure on the Prognosis of Postural Tachycardia Syndrome in Children - Wang, Shuo; Zou, Runmei; Cai, Hong; Wang, Cheng (Frontiers in Pediatrics, 2022)
Background To investigate the predictive value of heart rate (HR) and blood pressure (BP) on the prognosis of postural tachycardia syndrome (POTS) in children. Materials and Methods 53 cases of children aged 5 to 15 years who visited in the Pediatric Syncope Specialist Clinic of The Second Xiangya Hospital of Central South University for unexplained syncope or syncope precursor were diagnosed with POTS by head-up tilt test (HUTT) as the POTS group. 38 healthy children aged 5 to 16 years who underwent physical examination at the Child Health Care Clinic of the hospital in the same period were matched as controls (control group). The children with POTS were followed up after 3 months of treatment and were divided into good prognosis group (40 cases) and poor prognosis group (13 cases) according to the results of HUTT re-examination and whether the symptoms improved or not. HR and BP indicators were collected from each group at baseline and during HUTT. Results There were 91 research subjects, of which 45 are males, with a mean age of 11.52 ± 2.13 years. (1) HR at 5 and 10 min (HR 5 and HR 10, respectively), HR difference at 5 and 10 min (HRD 5 and HRD 10, respectively), and HR and BP product at 5 and 10 min (RPP 5 and RPP 10, respectively) were greater in the POTS group than in the control group (P < 0.01). (2) HR 5, HR 10, HRD 5, HRD 10, and RPP 10 in children with POTS were smaller in the good prognosis group than the poor prognosis group (P < 0.01). (3) The area under curve was 0.925 on the four combined indicators (HR 5, HR 10, HRD 5, and HRD 10), predicting a good prognosis of POTS, sensitivity of 99.99%, and specificity of 75.00%. Conclusions HR 5, HR 10, HRD 5, HRD 10, and RPP 10 and the four combined indicators (HR 5, HR 10, HRD 5, and HRD 10) had predictive value for the POTS prognosis in children. The predictive value of the four combined indicators for the POTS prognosis was better than that of the single HR 5, HRD 5, and RPP 10.